WAREHOUSING AND INVENTORY MANAGEMENT ANALYSIS : CASE STUDY TESLA. INC - Rizki Agung Ramadani; Berliyana Kesuma Hati; Zefri Setiawan (PT. Media Akademik Publisher, 2024)
Tesla’s innovative techniques for supply chain management and inventory control have positioned it as a leader in the electric vehicle industry. This paper explores the prevailing practices and proposes new strategies to address the challenging situation in Tesla’s inventory management. Key areas of concern include enhancing dealer collaboration, implementing advanced forecasting strategies, implementing hybrid inventory versions, and leveraging automation. The study also emphasizes the importance of robust sustainability and disaster management. The proposed solutions aim to improve accuracy, performance, and resilience while aligning with Tesla’s commitment to innovation and environmental obligations. The analysis highlights the challenging situation, benefits, and implications for stakeholders, including suppliers, clients, and the organization itself. Robust implementation of these strategies will enhance inventory stability, operational performance, and sustainability, thereby aiding Tesla’s long-term fulfillment in the competitive market.